Sost Deficiency does not Alter Bone’s Lacunar or Vascular Porosity in Mice - Mosey, Henry; Núñez, Juan A.; Goring, Alice; Clarkin, Claire E.; Staines, Katherine A.; Lee, Peter D.; Pitsillides, Andrew A.; Javaheri, Behzad (Frontiers in Materials, 2017)
SCLEROSTIN (Sost) is expressed predominantly in osteocytes acting as a negative regulator of bone formation. In humans, mutations in the SOST gene lead to skeletal overgrowth and increased bone mineral density, suggesting that SCLEROSTIN is a key regulator of bone mass. The function of SCLEROSTIN as an inhibitor of bone formation is further supported by Sost knockout (KO) mice which display a high bone mass with elevated bone formation. Previous studies have indicated that Sost exerts its effect on bone formation through Wnt-mediated regulation of osteoblast differentiation, proliferation and activity. Recent in vitro studies have also suggested that SCLEROSTIN regulates angiogenesis and osteoblast-to-osteocyte transition. Despite this wealth of knowledge of the mechanisms responsible for SCLEROSTIN action, no previous studies have examined whether SCLEROSTIN regulates osteocyte and vascular configuration in cortices of mouse tibia. Herein, we image tibiae from Sost KO mice and their wild-type (WT) counterparts with high resolution CT to examine whether lack of SCLEROSTIN influences the morphometric properties of lacunae and vascular canal porosity relating to osteocytes and vessels within cortical bone. Male Sost KO and WT mice (n = 6 /group) were sacrificed at 12 weeks of age. Fixed tibiae were analysed using microCT to examine cortical bone mass and architecture. Then, samples were imaged by using benchtop and synchrotron nanoCT at the tibiofibular junction. Our data, consistent with previous studies show that, Sost deficiency leads to significant enhancement of bone mass by cortical thickening and bigger cross-sectional area and we find that this occurs without modifications of tibial ellipticity, a measure of bone shape. In addition, our data show that there are no significant differences in any lacunar or vascular morphometric or geometric parameters between Sost KO mouse tibia and WT counterparts. We therefore conclude that the significant increases in bone mass induced by Sost deficiency are not accompanied by any significant modification in the density, organisation or shape of osteocyte lacunae or vascular content within the cortical bone. These data may imply that SCLEROSTIN does not modify the frequency of osteocytogenic recruitment of osteoblasts to initiate terminal osteocytic differentiation in mice.